Volume shrinkage during carbothermic reduction of low-grade iron ore containing goethite and coal composite - Setiawan, Agung; Ina Ermawati,; Anggraini, Farras; Abidin, Faizinal; Abdul Hapid,; Kawigraha, Adji; Harjanto, Sri; Rhamdhani, M. Akbar (Penerbit Universiti Kebangsaan Malaysia, 2022)
The volume shrinkage and reduction behavior of low-grade iron ore goethite during the solid-state carbothermic process was studied and compared to synthetic goethite. The carbothermic reduction process using low-grade coal as a reducing agent was carried out in the temperature range 1000-1200 °C up to 60 min of reaction time. The results demonstrated that the volume shrinkage, reduction degree, and metallization degree of reduced samples increase with increasing temperature and reaction time. Compared to the reduced samples using synthetic goethite, the volume shrinkage, reduction degree, and metallization degree of the reduced samples using iron ore are lower due to the presence of impurities in Sebuku iron ore concentrates, which include Mg, Mn, Al, and Si. The highest volume shrinkage observed at 1200 °C for 60 min reaction time for the reduced samples using iron ore and synthetic goethite was 63.57±0.57 and 76.51±1.53%, respectively. The observed phases at this point were metallic iron (Fem) and spinel (Fe,Mg)Al2O4. The volume shrinkage of the reduced samples was caused primarily by the weight loss due to carbon, oxygen, and combined water evaporation, as well as the sintering of gangue oxides and metallic iron particles, and partial melting of these phases.